Investigation on uranyl interaction with bioactive ligands. Synthesis and structural studies of the uranyl complexes with glycine and N-(2-mercaptopropionyl)glycine - Keramidas, Anastasios D.; Rikkou, Maria P.; Drouza, Chryssoula (My University, 2002)
Three new uranium(VI) compounds have been prepared with glycine (Hgly), N-(2-mercaptopropionyl)glycine (Hmpg) and 2,2′-dithiobis(N-propionylglycine) (tpg). The crystal structure of [UO2(Hgly)2Cl2] has been solved, revealing the uranium atom to be seven-co-ordinated. The two zwitterionic glycines are coordinated to uranium atom by the carboxylate groups, one in a monodentate and the other in a bidentate mode. Solid state studies and low temperature 1H, 13C, 2D COSY and HMQC solution NMR spectra of the [UO2(mpg)(CH3COO)], show that mpg coordinates uranium atom by the carboxylate group
Keywords: Carboxylic acids; Glycine; Ligands; Uranium; Infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Solid state; X-ray crystallography